Attachment as a Mediator Linking Childhood Maltreatment to Attributions in Adult Intimate Relationships. (October 2022) - Fitzgerald, Michael
Introduction: Childhood abuse has been linked to greater attachment insecurity in adulthood which has implications for adult romantic relationships. Abuse and attachment may particularly influence attributions of their partner's behavior. The current study examine adult attachment anxiety and avoidance as mediators linking childhood emotional, physical, and sexual abuse to attributions in adults currently in a romantic relationship.Method: A sample of 191 adults were recruited (mean age = 29.16, 71% White) and completed an online survey. Structural equation modeling was used to examine the indirect effects linking childhood abuse to attributions using bias corrected bootstrapping.Results: Findings from bootstrapped structural equation modeling indicated that attachment anxiety, but not avoidance, linked child emotional and physical abuse to attributions. Sexual abuse was directly, positively associated with attributions, independent of attachment and physical and emotional abuse.Conclusions: Clinicians may want to target anxious attachment in reducing negative attributions with a focus on how distal experiences of childhood emotional abuse may be impacting attachment security. Emotion focused couple therapy is a recommended intervention.